Psychotropic Effects of an Alcoholic Extract from the Leaves of Albizia zygia (Leguminosae-Mimosoideae) - Amoateng, P.; Osei-Safo, D.; Kukuia, K.K.E.; Adjei, S.; Akure, O.A.; Agbemelo-Tsomafo, C.; Adu-Poku, S.N.; Agyeman-Badu, K.Y. (Hindawi Publishing Corporation, Evidence-Based Complementary and Alternative Medicine, 2017)
Background. Albizia zygia is used in Ghanaian traditional medicine for the management of mental disorders. The present study tested the hypothesis that an extract of the leaves of Albizia zygia (AZE) may possess antipsychotic and antidepressant properties. Method. The novelty- and apomorphine-induced locomotor and rearing behaviours of AZE in mice were explored in an openfield observational test system. The effects of AZE in apomorphine-induced cage climbing test, extract-induced catalepsy, and haloperidol-induced catalepsy on mice were also investigated. Lastly, the forced swimming and tail suspension tests in mice were employed to screen the possible antidepressant effects of AZE. Results. AZE (100–3000mg/kg) showed signs of central nervous system (CNS) depression under observation, with no lethality, 24 h after treatment in mice. AZE (100–1000mg/kg) produced a significant decrease in the frequency of novelty- and apomorphine-induced locomotor activities in mice. The extract also significantly decreased the frequency and duration of apomorphine-induced climbing activities in mice. AZE, while failing to produce any cataleptic event in na¨ıve mice, significantly enhanced haloperidol-induced catalepsy at a dose of 1000mg/kg.However, AZE did not produce any significant antidepressant effects in the test models employed. Conclusion. The extract of Albizia zygia exhibited an antipsychotic-like activity in mice.
Article
Keywords: Psychotropic Effects; Alcoholic Extract; Albizia zygia (Leguminosae-Mimosoideae)